2022
DOI: 10.1002/mrd.23657
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal developmental expression and localization of apelin and apelin receptor protein in the ovary and uterus of mice

Abstract: Postnatal ovarian and uterine development is crucial to accomplished female fertility. Thus, the investigations of factors that present in pre-pubertal stages are important as it might be responsible for the regulation of ovarian and uterine function. Apelin, an adipokine and its receptor (APJ) are present in female reproductive organs. However, no study has reported its postnatal expression in uterus and ovary. Thus, we investigated the postnatal developmental changes in expression and localization of apelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…shown to be expressed in the uterine muscle of rats and mice (Anima et al, 2023;Balci et al, 2023;O'Carroll et al, 2000) and in the human uterine tissue apelin inhibits uterine contractility in vitro (Hehir & Morrison, 2012). Therefore, the deregulation of apelin system in the hyperandrogenized condition could also affect the contractility of oviduct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shown to be expressed in the uterine muscle of rats and mice (Anima et al, 2023;Balci et al, 2023;O'Carroll et al, 2000) and in the human uterine tissue apelin inhibits uterine contractility in vitro (Hehir & Morrison, 2012). Therefore, the deregulation of apelin system in the hyperandrogenized condition could also affect the contractility of oviduct.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the localization of apelin, APJ, HSP70, BCL2, active caspase3, and phospho-Akt routine immunohistochemistry was followed (Anima et al, 2023) Once mounted with DPX, the slides were examined and photographed using camera-mounted binocular microscope (Model DC.1359 F100, Euromex). For semi-quantification, ImageJ software was used to quantify the stained area.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The Nanoparticles used in this experiment, Copper (ll) oxide (Cat#544868-5G), were purchased from Sigma-Aldrich Chemicals Pvt Ltd. The purchased CuNPs were already characterized by TEM analysis and was <50 nm in size (Anima et al, 2023;Nicy et al, 2022).…”
Section: Chemicalsmentioning
confidence: 99%
“…It has been show that CuNPs can enter the placental barrier and causes nutritional imbalance and liver dysfunction in fetus of pregnant rats (Luo et al, 2020). Our recent study has shown that CuNPs treatment increases the oxidative stress, and induces degenerative changes in mice uterus (Anima et al, 2023). Intraperitoneal injection with 0.5, 20, and 40 mg/kg/bw of CuNPs for 3, 6, and 9 days have negative effect on the reproductive organs of albino rats, where there was an increase in sperm abnormality and decrease in the sperm viability (Al-Bairuty & Taha, 2016).…”
mentioning
confidence: 91%
“…PBS was used to wash off the unbound primary antibody and incubated with secondary antibody (1:400, goat anti-rabbit, cat# PI-1000, Vector Laboratories, Burlingame, CA, USA). The antibodies for apelin and apelin receptors (APJ) have been used for the localization of these proteins in mice [39]. The slides were then proceed in DAB solution containing 0.6 mg/mL solution of 3, 3-diaminobenzidine tetra hydrochloride Dihydrate (DAB) in Tris-HCl (pH 7.6) and 0.01% H 2 O 2 until brown color developed and the reaction was stopped by distilled water.…”
Section: Immunohistochemistrymentioning
confidence: 99%